2018
DOI: 10.1159/000492264
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Tissue Trib3 Links Obesity with Insulin Resistance by Autophagic Degradation of AKT2

Abstract: Background/Aims: Obesity is a serious health risk factor strongly associated with insulin resistance and type 2 diabetes; however, the underlying mechanisms associating obesity with insulin resistance remain unknown. In this study, we explored the physiological role of Trib3 in regulating glucose metabolism in skeletal muscle tissues in a Trib3 transgenic mice model. Methods: Glucose metabolism in transgenic mice overexpressing Trib3 specifically in the skeletal muscle was examined by glucose/insulin tolerance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 52 publications
2
10
0
Order By: Relevance
“…Whereas autophagy has unique effects on metabolism in different tissues [12,13,14,15,16,17,18,45,46,47], it appears that the major function of autophagy in adipose tissue is the regulation of mitochondrial homeostasis [48]. Intriguingly—in line with previous observations in cardiac and skeletal muscle [49,50]—we found that the expression levels of mitochondrial markers were lower in the BAT of older mice than younger mice.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Whereas autophagy has unique effects on metabolism in different tissues [12,13,14,15,16,17,18,45,46,47], it appears that the major function of autophagy in adipose tissue is the regulation of mitochondrial homeostasis [48]. Intriguingly—in line with previous observations in cardiac and skeletal muscle [49,50]—we found that the expression levels of mitochondrial markers were lower in the BAT of older mice than younger mice.…”
Section: Discussionsupporting
confidence: 88%
“…For acclimation, control and ATG7B KO mice were individually housed two days prior to the metabolic cage study. The oxygen (O 2) consumption, carbon dioxide (CO 2) production, locomotor activity, respiratory exchange ratio (RER) and food intake of individually housed mice were monitored using an indirect calorimeter (Columbus Instruments, Columbus, OH, USA) and analyzed as described previously [47]. For β3-adrenergic receptor stimulation experiments, 100 μg/g of CL316,243 (Sigma-Aldrich) was intraperitoneally injected.…”
Section: Methodsmentioning
confidence: 99%
“…9 Trb3 is thought to be up-regulated in response to oxidative stress, and then bind to Akt2 for accelerating its degradation via autophagy. 31 In the present study with Akt2-KO mice, we also found that of downstream gluconeogenic pathways. 18 In the present study, phosphorylation of total Akt, probably mainly Akt1, indeed increased in the heart of Akt2-KO mice compared with WT mice, but did not further increase in the heart of MT-TG/Akt2-KO mice compared to Akt2-KO mice, and even trended lower in females (Figure 6B).…”
Section: Discussionsupporting
confidence: 71%
“… 9 Trb3 is thought to be up‐regulated in response to oxidative stress, and then bind to Akt2 for accelerating its degradation via autophagy. 31 In the present study with Akt2‐KO mice, we also found that cardiac overexpression of MT was able to preserve almost normal levels of Akt2 downstream glucose transport and metabolism‐associated molecule expression and function, and prevent oxidative damage in MT‐TG/Akt2‐KO mice, therefore, the MT prevention of DCM in Akt2‐KO mice could not be mediated by its preservation of Akt2 expression and function through suppressing Trb3 as Akt2 negatively regulator, so alternative mechanisms must be implicated.…”
Section: Discussionmentioning
confidence: 99%
“…Yan reported that palmitic acid (PA), an important FFA constituent in GCs can induce endoplasmic reticulum stress (ERs) in a human hepatic cell line, accompanied by a signi cant induction of tribbles of pseudokinase 3 (TRIB3) expression, which was associated with decreased levels of phosphorylated Akt (p-Akt) [12]. Moreover, some other reports showed that TRIB3 induces abnormal Akt phosphorylation under high PA conditions in various cells [13][14][15]. On the other hand, TRIB3 was involved in cell proliferation and fatty acid oxidation signaling in bovine cumulus cells, which are also derived from follicular cells as granulosa cells and played a key role in oocyte meiotic resumption regulation [16].…”
Section: Introductionmentioning
confidence: 99%